Experimental Study on Hypersonic Boundary Layer Transition of Re-entry Vehicle HOPE-X - SUZUKI, Akio; OGASAWARA, ko (Transactions of the Japan Society of Mechanical Engineers Series B, 1998)
Boundary layer transition is an important subject for the thermal design of re-entry vehicle because aerodynamic heating rate increases very rapidly with the transition. As so many factors affect the boundary layer transition, this subject is still unsolved problem even today, therefore experimental studies are conducted on boundary layer transition of windward surface of HOPE-X. It was ascertained the transition correlation parameter used for Space Shuttle design is applicable as an approximate basis for HOPE-X, though parametric value differs depending on vehicle configuration.